Quantification of coverage, uniformity and residues for CVD monolayer graphene transfer process based on image analysis (2023)
ABSTRACT: The use of CVD-grown graphene requires a transfer method to transport this material from the metal foil on top of which it is grown onto a target substrate. In many cases this transfer changes its properties, leading to variations from one zone of the target substrate to another. Here we present a simple semi-automatic method for a quantitative study of the coverage, uniformity and residues of graphene transferred onto Si/SiO2 substrates whose operation is not dependent on costly equipment, making it low-cost oriented. The method can be extrapolated to different target substrates, e.g., ITO-coated glass, and serves as an evaluation tool for graphene transfer processes. This is achieved by calculating a figure of merit, based on 2 proposed quantitative parameters (accounting for the coverage and the uniformity of the transferred graphene), while simultaneously determining the residues left by the transfer substrate using MATLAB-based image analysis of optical microscopy images. To corroborate the proposed method, a comparison between polydimethylsiloxane (PDMS), thermal release tape (TRT) and polymethylmethacrylate- (PMMA) assisted transfer processes is performed, demonstrating that the methodology is valid for all cases. Coverages over 80 % are obtained, being in good agreement with results from the same transfer processes studied via Raman mapping.